Research and Development of Overhead Catenary Maintenance Operation CarApplied for Centralized Maintenance Mode - ZHAO Li; LI Yongzhe; REN Taolong (机车电传动)
Aiming at the problems of operation low efficiency, long-time application for skylight in traditional operation mode, anoverhead catenary maintenance operation car applied for the centralized maintenance mode was introduced, test of which was introduced.The test results indicated that the maintenance operation car satisfied related standards and design requirements.